Corporate finance theory and practice - Vernimmen, Pierre; Quiry, Pascal; Dallocchio, Maurizio; Le Fur, Yann; Salvi, Antonio (Wiley, 2018)
Corporate Finance has long been a favorite among both students and professionals in the field for its unique blend of theory and practice with a truly global perspective. The fact that the authors are well-known academics and professionals in the world of mergers and acquisitions (M&A) and investment explains this popularity. This new Fifth Edition continues the tradition, offering a comprehensive tour of the field through scenario-based instruction that places concept and application in parallel. A new chapter has been added, devoted to the financial management of operating buildings that aims to answer questions such as, “to own or to rent?” “variable or fixed rents?” etc. The book’s companion website features regularly updated statistics, graphs and charts, along with study aids including quizzes, case studies, articles, lecture notes and computer models, reflecting the author team’s deep commitment to facilitating well-rounded knowledge of corporate finance topics. In addition, a monthly free newsletter keeps the readers updated on the latest developments in corporate finance as well as the book’s Facebook page, which publishes a post daily. Financial concepts can be quite complex, but a familiar setting eases understanding while immediate application promotes retention over simple memorization. As comprehensive, relevant skills are the goal, this book blends academic and industry perspective with the latest regulatory and practical developments to provide a complete corporate finance education with real-world applicability. -- Provided by publisher.